TARBIYAH AN-NABAWIYAH PERSPEKTIF PROF. DR. SAYYID MUHAMMAD BIN ALAWI AL-MALIKI DALAM KONTEKS MODERASI BERAGAMA - Muhammad Helmi; Abdulloh (Journal Multicultural of Islamic Education, 2025)
This article discusses the thoughts of Prof. Dr. Sayyid Muhammad bin Alawi al-Maliki regarding Tarbiyah An-Nabawiyah in the context of religious moderation. This study adopts a library research approach, with data collection sourced from various relevant literature such as Mafahim Yajibu an-Tusohhah and collecting important information from previously collected sources. The next stage is data analysis. The results of the study show that religious moderation is an important contribution to grounding peaceful, just, and inclusive Islam. Through a cool da'wah approach, balanced education, and harmonious social relations. he showed that Islam can be a force that unites, not divides. In the midst of increasing extremism and intolerance, his teachings are very relevant to be used as a reference in building a moderate and harmonious religious life.